2018
DOI: 10.3389/fpls.2018.01552
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of Transgenic cry1Ab/c Rice Under Saline-Alkaline Soil Condition

Abstract: The environmental release and biosafety of transgenic Bt crops have attracted global attention. China has a large area of saline-alkali land, which is ideal for large-scale production of Bt transgenic rice. Therefore an understanding of the fitness of Bt transgenic rice in saline-alkaline soils and the ability to predict its long-term environmental effects are important for the future sustainable use of these crops. In the present study, we aimed to evaluate the fitness of cry1Ab/c transgenic rice in both farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Under high and low temperature, drought, and flooding stress habitats, the expression of the exogenous Bt protein in transgenic maize was significantly lower than that under normal habitats (Trtikova et al, 2015). At the same time, the expression of exogenous Bt protein in transgenic rice in habitats stressed with NaCl, flooding (Luo et al, 2008), low, medium, and high salinity (Luo et al, 2017;Fu et al, 2018) showed a decreasing trend compared to the expression in normal habitats. In our study, we compared the content of Bt protein in transgenic cotton plants at different growth stages under different environments.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Under high and low temperature, drought, and flooding stress habitats, the expression of the exogenous Bt protein in transgenic maize was significantly lower than that under normal habitats (Trtikova et al, 2015). At the same time, the expression of exogenous Bt protein in transgenic rice in habitats stressed with NaCl, flooding (Luo et al, 2008), low, medium, and high salinity (Luo et al, 2017;Fu et al, 2018) showed a decreasing trend compared to the expression in normal habitats. In our study, we compared the content of Bt protein in transgenic cotton plants at different growth stages under different environments.…”
Section: Discussionmentioning
confidence: 89%
“…In saline-alkaline soils, the insect-resistant transgenic Cry1C* rice T1C-19 showed a strong reproductive capacity, and significantly reduced the loss of yield caused by insects, therefore leading to a higher yield than that of its non-transgenic counterparts MH63 grown (Fu and Liu, 2020). The vegetative and reproductive growth abilities showed a significantly higher fitness cost for the Cry1Ab/c transgenic rice, Huahui1, than that for the parental rice, Minghui63, grown under the same normal farmland and saline-alkaline soil conditions (Fu et al, 2018). Under the same drought conditions, the yield of GM insect-resistant cotton, RCHB 708, was significantly higher than that of non-GM cotton, LRA 5166, and GM cotton showed a fitness advantage (Sankaranarayanan and Nalayini, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If the aforementioned photosynthetic and stress resistance proteins are affected, the photosynthesis and stress resistance responses themselves could also be modulated. Herein, expression of an extra exogenous Cry1Ab/c protein in transgenic rice Huahui-1 considerably affected the photosynthetic efficiency and stress resistance of this strain relative to those of parent rice MH63 (Fu et al, 2018), and accordingly, we propose that the observed unintended effects might be a result of the interactions between the Cry1Ab/c protein and endogenous photosynthesis and stress resistance proteins. However, not all interactions between Cry1Ab/c and interacting endogenous proteins induced phenotypic effects, and thus, future research should use other molecular biological, physiological, and biochemical means, such as transcriptome and proteome methods, to further explore the transcription and protein expression of aforementioned photosynthetic and stress resistance proteins that interact authentically and strongly with Cry1Ab/c.…”
Section: Validation Of the Interactions Between Cry1ab/c And Candidatmentioning
confidence: 93%
“…However, there is currently insufficient empirical evidence to corroborate these theories. Although the crop cannot express naturally the exogenous proteins, the transgenic crops could express these proteins through integrating exogenous genes into the crop genome in all tissues throughout the growth stages (Fu et al, 2018), so these exogenous proteins might potentially interact with endogenous proteins to produce unintended biological effects in the transgenic crop. To date, however, the aforementioned issue has not raised sufficient concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation